Osing Language in Intergenerational Discourse: A Sociolinguistic Case Study from Kemiren Village - Fitri Nur Faizah; Uci Kusumawati; Ahmadintya Anggit Hanggraito -; Mochammad Khairul Fatkhurahman; Robi Ilhami (UNIB Press, 2025)
Kemiren Village in Banyuwangi Regency is a vital site for preserving the Osing language, a key element of the region's cultural identity. However, the influence of modernization, national language policies, and digital media has led to a decline in Osing usage, especially among younger generations. This study explores generational differences in Osing language use across Millennials, Generation Z, and Generation Alpha. Using a descriptive qualitative method, data were collected through interviews, observations, and document analysis, and then analyzed using Bogdan and Biklen's qualitative analysis framework. The findings reveal that Millennials still actively use Osing in both family and community settings, but a shift toward Indonesian is evident. Among Generation Z, Osing is used primarily in informal contexts, whereas among Generation Alpha, it is used minimally, with a preference for Indonesian and foreign languages. Despite this decline, various revitalization efforts—such as digital promotion of Osing music, cultural tourism events, and local government policies that integrate Osing into school curricula—demonstrate ongoing community and institutional commitment. The study underscores the need for a comprehensive strategy that incorporates cultural, educational, technological, and familial dimensions to ensure the continued use and transmission of the Osing language and to safeguard Kemiren's intangible cultural heritage.